2011
DOI: 10.1186/1746-4358-6-4
|View full text |Cite
|
Sign up to set email alerts
|

Work related determinants of breastfeeding discontinuation among employed mothers in Malaysia

Abstract: BackgroundThis cross-sectional study assesses factors that contribute to discontinuing breastfeeding among employed mothers in Malaysia.MethodsA structured questionnaire was used in conducting this study involving all government health clinics in Petaling district between July and September 2006. Respondents were Malaysian women with children between the ages of six to twelve months who were formally employed. Factors studied were selected socio-demographic and work-related characteristics.ResultsFrom a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
2
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 5 publications
6
63
2
11
Order By: Relevance
“…This finding supports study conducted in east Ethiopia which revealed Nonexclusive breastfeeding was more likely to be practiced by mothers who had no access to health facility AOR (95% CI) = 2.9 (1.9,4.3) [10] and Nigeria which revealed that mothers who visited health professionals, or made 4 or more antenatal clinic visits were significantly more likely to exclusively breastfeed their babies, and these findings suggests that appropriate message about breastfeeding are being delivered by antenatal care staff [11]. In the qualitative study, those mothers had contact with health professionals have adequate knowledge regarding EBF.…”
Section: Determinates Of Exclusive Breast Feedingsupporting
confidence: 78%
See 1 more Smart Citation
“…This finding supports study conducted in east Ethiopia which revealed Nonexclusive breastfeeding was more likely to be practiced by mothers who had no access to health facility AOR (95% CI) = 2.9 (1.9,4.3) [10] and Nigeria which revealed that mothers who visited health professionals, or made 4 or more antenatal clinic visits were significantly more likely to exclusively breastfeed their babies, and these findings suggests that appropriate message about breastfeeding are being delivered by antenatal care staff [11]. In the qualitative study, those mothers had contact with health professionals have adequate knowledge regarding EBF.…”
Section: Determinates Of Exclusive Breast Feedingsupporting
confidence: 78%
“…For quantitative: To estimate the prevalence of EBF a single population proportion formula was used with the following assumptions: national prevalence of exclusive breastfeeding at age 4-5 month was 0.32 [9][10][11][12][13][14][15][16][17], margin of error 5% (desired precision between sample and population parameter), and a 5% contingency for the nonresponse. Final sample size was 354.…”
Section: Sample Size Determinationmentioning
confidence: 99%
“…The lack of support from the workplace may be a reason why these mothers decide to discontinue or not to consider breastfeeding, even though they had a positive attitude toward breastfeeding. Amin et al 6 in their study conducted in 2006 concluded that providing a more conducive environment for breastfeeding would encourage a higher rate of exclusive breastfeeding among working mothers.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted among Malaysian women aged between 25-35 years found that majority of working mothers had stopped breastfeeding in less than three months. In addition to this, Chinese and Indian mothers have higher risk of discontinuing breastfeeding compared to Malay mothers (Amin et al, 2011). This might be caused by inadequate breastfeeding facilities provided at workplace.…”
Section: Introductionmentioning
confidence: 99%